Healthy Lung Vessel Morphology Derived From Thoracic Computed Tomography - Pienn, Michael; Burgard, Caroline; Payer, Christian; Avian, Alexander; Urschler, Martin; Stollberger, Rudolf; Olschewski, Andrea; Olschewski, Horst; Johnson, Thorsten; Meinel, Felix G.; Bálint, Zoltán (Frontiers in Physiology, 2018)
Knowledge of the lung vessel morphology in healthy subjects is necessary to improve our understanding about the functional network of the lung and to recognize pathologic deviations beyond the normal inter-subject variation. Established values of normal lung morphology have been derived from necropsy material of only very few subjects. In order to determine morphologic readouts from a large number of healthy subjects, computed tomography pulmonary angiography datasets, negative for pulmonary embolism and other thoracic pathologies, were analyzed using a fully-automatic, in-house developed artery/vein separation algorithm. The number, volume, and tortuosity of the vessels in a diameter range between 2-10mm were determined. Visual inspection of all datasets was used to exclude subjects with poor image quality or inadequate artery/vein separation from the analysis. Validation of the algorithm was performed manually by a radiologist on randomly selected subjects. In 123 subjects (men/women:55/68), aged 59±17 years, the median overlap between visual inspection and fully-automatic segmentation was 94.6% (69.2-99.9%). The median number of vessel segments in the ranges of 8-10mm, 6-8mm, 4-6mm, and 2-4mm diameter was 9, 34, 134, and 797, respectively. Number of vessel segments divided by the subjects’ lung volume was 206 vessels/L with arteries and veins contributing almost equally. In women this vessel density was about 15% higher than in men. Median arterial and venous volumes were 1.52% and 1.54% of the lung volume, respectively. Tortuosity was best described with the sum-of-angles metric and was 142.1rad/m (138.3-144.5rad/m). In conclusion, our fully-automatic artery/vein separation algorithm provided reliable measures of pulmonary arteries and veins with respect to age and gender. There was a large variation between subjects in all readouts. No relevant dependence on age, gender, or vessel type was observed. These data may provide reference values for morphometric analysis of lung vessels.